2017
DOI: 10.1194/jlr.m077792
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and hydrolysis of serine dipeptide lipids of Bacteroidetes bacteria in human arteries: relationship to atherosclerosis

Abstract: Multiple reaction monitoring-MS analysis of lipid extracts from human carotid endarterectomy and carotid artery samples from young individuals consistently demonstrated the presence of bacterial serine dipeptide lipid classes, including Lipid 654, an agonist for human and mouse Toll-like receptor (TLR)2, and Lipid 430, the deacylated product of Lipid 654. The relative levels of Lipid 654 and Lipid 430 were also determined in common oral and intestinal bacteria from the phylum Bacteroidetes and human serum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 46 publications
2
57
0
Order By: Relevance
“…For example, bacteria of the phylum Bacteroidetes produce serine dipeptide lipids that are recognized by TLR‐2 . These lipid forms are common in some P. gingivalis strains and they have also been recovered in carotid endarterectomy samples .…”
Section: Other Bacterial Antigens As Mediatorsmentioning
confidence: 99%
“…For example, bacteria of the phylum Bacteroidetes produce serine dipeptide lipids that are recognized by TLR‐2 . These lipid forms are common in some P. gingivalis strains and they have also been recovered in carotid endarterectomy samples .…”
Section: Other Bacterial Antigens As Mediatorsmentioning
confidence: 99%
“…An interesting study, assessing the relationship between serine dipeptide lipids of Bacteroidetes bacteria in human arteries and atherosclerosis, was recently published in the Journal of Lipid Research [11]. The new ideas advocated here add to our understanding of the capacity of such bacteria to contribute to atherosclerosis.…”
mentioning
confidence: 99%
“…The relative abundance of these lipids was examined in oral and intestinal bacteria from the phylum Bacteroidetes and from human serum and brain samples from healthy adults [11]. These analyses showed that the median Lipid 430/Lipid 654 ratio in carotid endarterectomy samples was significantly higher than the median lipid ratio in extracts from common oral and intestinal Bacteroidetes bacteria, as well as in extracts from serum and brain samples from healthy subjects.…”
mentioning
confidence: 99%
See 2 more Smart Citations